Complicity - Banks, Iain, 1954-2013 (CNIB, 2006)
Cameron Colley is a journalist on an Edinburgh paper, totally into his job, a computer game called Despot and an intermittently sado-masochistic love affair. He is on the brink of uncovering the grandfather of all conspiracies, but while he's researching a series of bizarre past deaths, the police are investigating some that are still going on and Cameron, complicit as he seems to be, may be able to help them with their enquiries. Strong language. 1993.